2008
DOI: 10.1002/adma.200703009
|View full text |Cite
|
Sign up to set email alerts
|

Core/Shell Nanoparticles as Electrocatalysts for Fuel Cell Reactions

Abstract: Nanoscale catalysis depends on spatial and surface arrangements of atoms. The synthesis of core/shell nanoparticles by synthetic approaches, the characterization of the core/shell nanostructures in terms of the relative core/shell compositions, and the demonstration of the electrocatalytic activities for fuel cell reactions (see figure), as reported in this Communication, have important implications to the design of desired nanoscale catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
169
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(173 citation statements)
references
References 48 publications
3
169
1
Order By: Relevance
“…In recent years, there has been a growing interest in bimetallic hybrid NPs, since their chemical and physical properties are different from those for both the bulk metals and their monometallic NP counterparts [15][16][17][18][19][20]. Toshima et al have reported that core-shell bimetallic NPs exhibit a higher catalytic activity than the monometallic counterparts because the catalytic activity of the shell atoms can be electronically influenced by the core atoms [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in bimetallic hybrid NPs, since their chemical and physical properties are different from those for both the bulk metals and their monometallic NP counterparts [15][16][17][18][19][20]. Toshima et al have reported that core-shell bimetallic NPs exhibit a higher catalytic activity than the monometallic counterparts because the catalytic activity of the shell atoms can be electronically influenced by the core atoms [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between the size, structure and catalytic activities was revealed over several interesting systems, e.g., PtNi, PtCo and AuPt [12,13,23,27,28]. Gold-platinum (AuPt) nanoalloys serve as an intriguing system in terms of the unique synergistic properties [12,27,28].…”
Section: Bimetallic Nanoalloy Catalystsmentioning
confidence: 99%
“…The size and composition of the nanoparticles produced by thermochemical processing are controllable. As shown for a series of binary and ternary alloy nanoparticle systems in Table 1 [12][13][14][15][16][17][23][24][25][26][27][28][29][30][31][32][33][34][35], the catalysts prepared by the molecularly-mediated synthesis and thermochemical processing methods have demonstrated enhanced catalytic and electrocatalytic properties for oxygen reduction reaction (ORR), methanol oxidation reaction (MOR), and ethanol oxidation reaction (EOR), etc. …”
Section: Synthesis and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold-based nanoalloys (or gold alloy nanoparticles) are attracting growing attention due to their specific properties as optical [3], catalytic [2] and electro-catalytic [4] materials. In heterogeneous catalysis, bimetallic gold nanoparticles have shown high reactivity in a number of catalytic reactions including the direct synthesis of hydrogen peroxide from H 2 and O 2 [5,6], synthesis of vinyl acetate [7], selective hydrogenation of butadiene [8] and so forth.…”
Section: Introductionmentioning
confidence: 99%